Memorias cátedra abierta teoría económica (2008)
For the coordination of the Area of Economic Theory, in the Department of Economics, it is a great pleasure to present this publication to the university community, as a result of an effort started in 2006, in order to show the papers and investiga¬tions developed by professors of this field. The genesis of this idea was the opening of a formal and permanent academic space, called Opened Chair in Economic Theory, which runs each semester, where University’s professors and students participate. In this fist publication we put in consideration of the academic community the results of the Chair, done during the semesters 1 and 2, 2006. They are in total 5 conferences: Economic distribution. A look from dynamic justice; Historiography of neo¬classical demand theory; A general vision of the Austrian school; Transaction costs: a not so recent discovery; Approach to the Karl Marx’s theory of circulation costs; The solidarity as a production factor from comprehensive economic theory. We hope this document becomes an authorized consulting source for professors and students, not only for people who work in this field, but for all people interested in economic theory